Corrosion Analysis on AMS 4050 Aluminum Metal in an Extreme Acid Rain Environment by Weight Loss Method - Arwati, I Gusti Ayu; Alva, Sagir; Fadilah, Arif; Maryani, Yeyen (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2021)
AMS 4050 aluminum metal which is a type of aluminum, with no Zn content, that composed of 5.7 - 6.7%Cu 2 - 2.6%, Mg 1.9 - 2.6%, Zr 0.15%, Si 0.15% and Mn 0.1% others 0.15% each. The advantage of aluminum is that it weighs only 2.7 gr / cm3, corrosion resistant, good electrical and heat transmitter, easy to fabricate or forge. This AMS 4050 material is widely used in the expansion industry to be used as an aircraft frame. MS 4050 aluminum is more resistant to cracking than other types of aluminum, however cracks can still occur due to corrosion due to acid rain. The test method used to calculate the corrosion rate is the weight loss method. The corrosion rate test results obtained with mean values for immersion of 1, 2, 3, and 4 weeks were 0.03, respectively; 0.07; 0.1 and 0.12 mg / cm2 h. EDX test results showed that the aluminum content in AMS 4050 metal decreased by 18.18%.